SOSIALISASI “LAWAN PERUNDUNGAN” SEBAGAI UPAYA EDUKASI DAN PERLINDUNGAN ANAK DI SDN 168 DESA MAMPUN BARU, MERANGIN - Widia Putri Febriani; Ditya Putri Wulansari; Habibi; Rizki Apriadi Bahri; Lasmini (Hira Institute, 2025)
Bullying remains a serious problem in elementary schools and negatively impacts children's emotional, social, and academic development. This Community Service activity aims to increase students' understanding and awareness of bullying through the